Experiencing a Severe Weather Event Increases Concern About Climate Change - Bergquist, Magnus; Nilsson, Andreas; Schultz, P. Wesley (Frontiers in Psychology, 2019)
The hypothesis that experiencing extreme weather events can affect environmental concerns have long been discussed, yet rarely investigated. In a unique before and after design, 122 residents in Florida USA answered survey questions before and after experiencing hurricane Irma in September, 2017. After experiencing Irma, Floridians reported higher levels of negative emotions when thinking about climate change, a strengthened belief that Irma was caused by global warming, and they expressed greater willingness to sacrifice (e.g., pay higher taxes for the sake of the environment). In addition, a mediation analysis found that for extreme weather experiences to result in pro-environmental actions, people need to feel that this experience was negative and think that they ought to do something about climate change.